Preferences for wealth taxation: Design, framing and the role of partisanship - Malte Chirvi; Cornelius Schneider (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
Empirical literature on preferences for wealth taxation almost exclusively focuses on either the emotionally loaded estate tax or rather general concepts of redistributive preferences. Yet, it remains unclear whether the exceptional opposition towards the estate tax is applicable to other instruments of net wealth taxation. This study presents, to our knowledge, the first investigation of how individuals want to tax wealth - across a variety of tangible wealth tax instruments. In doing so, we particularly test for the presence of framing effects, incidence concentration and the role of wealth characteristics within the different tax configurations. For this, we conducted a factorial vignette survey experiment with over 3,200 respondents on Amazon's Mechanical Turk (MTurk). Each respondent was randomized into one of four burden-equivalent wealth tax instruments: an estate tax, a one-time wealth tax, a decennial wealth tax or a yearly wealth tax. Subsequently we asked each respondent to state her preferred overall lifetime tax burden for a set of hypothetical individuals. Our findings yield several interesting insights. First, we find that the exceptional opposition towards the estate tax is not applicable to other instruments of wealth taxation and is only valid for certain subgroups. In general, our empirical findings provide preferred tax rates between 12.8 to 14.9 percent of overall lifetime tax burden. Second, we document an exceptional opposition towards the mere name "estate tax" in relation to equivalent wealth tax instruments for certain subgroups. Republicans particularly reject the estate tax with a lower proposed effective tax rate of around 3.1 percentage points compared to all other wealth taxes - even the perfectly congruent one-time wealth tax. Third, we uncover the influence of normative preferences for specific design features on the support for a wealth tax. Proposed effective tax rates of the estate tax and the one-time wealth tax show a significant progressivity, whereas no progressivity can be observed for both periodical taxes. The presence of children has an especially significant negative effect in one-off wealth taxes at the end of the lifetime.
Keywords: C90; D31; D72; H2; 330; Wealth taxation; Preferences for taxation; Misinformation; Randomized experiment